2016
DOI: 10.1113/ep085915
|View full text |Cite
|
Sign up to set email alerts
|

Does attenuated skin blood flow lower sweat rate and the critical environmental limit for heat balance during severe heat exposure?

Abstract: Attenuated skin blood flow (SkBF) is often assumed to impair core temperature (Tc) regulation. Profound pharmacologically-induced reductions in SkBF (~85%) lead to impaired sweating but whether the smaller attenuations in SkBF (~20%) more associated with ageing and certain diseases lead to decrements in sweating and maximum heat loss potential is unknown. Seven healthy males (28±4y) completed a 30-min equilibration period at 41°C and a vapour pressure (Pa) of 2.57 kPa followed by incremental steps in Pa of 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
2
22
1
Order By: Relevance
“…However, interventions or conditions that affect local measures of cutaneous blood flow do not always similarly affect whole-limb measures. For example, we have observed that iso-osmotic dehydration (Cramer, Gagnon, Crandall, & Jay, 2017) and age reduce local cutaneous, but not whole-limb, vascular conductance during heat exposure. Along these lines, Stanhewicz et al (2013) reported that a dose of oral sapropterin increases both local cutaneous vascular conductance and forearm vascular conductance during passive heating in older adults.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, interventions or conditions that affect local measures of cutaneous blood flow do not always similarly affect whole-limb measures. For example, we have observed that iso-osmotic dehydration (Cramer, Gagnon, Crandall, & Jay, 2017) and age reduce local cutaneous, but not whole-limb, vascular conductance during heat exposure. Along these lines, Stanhewicz et al (2013) reported that a dose of oral sapropterin increases both local cutaneous vascular conductance and forearm vascular conductance during passive heating in older adults.…”
Section: Discussionmentioning
confidence: 88%
“…The critical humidity inflection point is an indicator of maximum heat loss potential (Kamon & Avellini, ; Kenney & Zeman, ; Kenney, Mikita, Havenith, Puhl, & Crosby, ). We have previously demonstrated that, in young adults, furosemide‐induced reductions in cutaneous blood flow do not affect the critical humidity inflection point for core temperature (Cramer et al., ). As such, conditions or interventions that elicit physiologically relevant reductions or increases in cutaneous blood flow have little to no effect upon maximum heat loss potential under extreme heat conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…; Cramer et al. ). Interestingly, an interaction was found between time and trial in T re and T sk , suggesting thermoregulatory mechanisms that are prompted during exercise manage heat strain more efficiently when euhydrated compared to dehydrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although not significant, SBF was lower during the DEH trial, which DEH and heat stress may independently and concomitantly reduce SBF and heat dissipation (Gonzalez-Alonso 1998) and ultimately may impair aerobic performance (Kenefick et al 2010). However, reductions in SBF do not necessarily result in impaired thermoregulation (Vroman et al 1983;Cramer et al 2017). Interestingly, an interaction was found between time and trial in T re and T sk , suggesting thermoregulatory mechanisms that are prompted during exercise manage heat strain more efficiently when euhydrated compared to dehydrated.…”
Section: Pre-interventionmentioning
confidence: 99%